High Prudent diet factor score predicts lower relapse hazard in early multiple sclerosis - Simpson-Yap, S.; Oddy, W.H.; Taylor, B.; Lucas, R.M.; Black, Lucinda; Ponsonby, A.L.; Blizzard, L.; van der Mei, I.; Dear, K.; Dwyer, T.; Broadley, S.; Kilpatrick, T.; et al. (SAGE PUBLICATIONS LTD, 2021)
Background: Dietary patterns and their association with subsequent clinical course have not been well studied in early multiple sclerosis (MS). Objectives: To describe dietary patterns in people in 5 years following first clinical demyelination and assess associations with MS conversion and relapse. Methods: This study included baseline food frequency questionnaire dietary intake (entry to the Ausimmune Study) and 5-year follow-up; iterated principal factor analysis was applied. MS conversion and relapse risks were assessed by Cox proportional hazards models, adjusted for age, sex, study site, education, body mass index (BMI), smoking and omega-3 supplement use. Results: In cases with a first clinical diagnosis of central nervous system (CNS) demyelination, we identified three major dietary patterns, ‘Prudent’, ‘High-Vegetable’ and ‘Mixed’, explaining 43%, 37% and 24% of diet variance in dietary intake, respectively. Fruits, vegetables, fish, wholegrains and nuts loaded highly on the Prudent pattern, starchy vegetables and legumes on the High-Vegetable pattern, and meats and alcohol on the Mixed pattern. Diet factor scores were not associated with MS conversion risk. Those with baseline Prudent scores above the median had significantly lower relapse risk (adjusted hazard ratio = 0.54, 95% confidence interval (CI) 0.37, 0.81) with some evidence of a plateau effect. Conclusion: Prudent diet factor score above the median was prospectively associated with lower relapse risk in the 5 years following the first clinical demyelinating event.